Advancing Research on Corporate Sustainability: Off to Pastures New or Back to the Roots?. (February 2017) - Hahn, Tobias; Figge, Frank; Aragón-Correa, J. Alberto; Sharma, Sanjay
Over the last two decades, corporate sustainability has been established as a legitimate research topic among management and organization scholars. This introductory article explores potential avenues for advances in research on corporate sustainability by readdressing some of the fundamental aspects of the sustainability debate and approaching some novel perspectives and insights from outside the corporate sustainability field. This essay also sketches out how each of the six articles of this special issue contribute to the literature by going back to some of the conceptual roots of sustainability and/or by offering novel perspectives for research on corporate sustainability. As these six articles and the outlook on future research opportunities show, broadening the inquiry of corporate sustainability in terms of topics, theories, and methodologies holds considerable potential to improve our understanding of how decision makers and organizations respond to sustainability.